ETHNOBOTANY OF KEMANG (Mangifera kemanga Blume.) AS IDENTITY FLORA OF BOGOR REGENCY - Beti Septiana Darsono; Agus Hikmat; Rinekso Soekmadi (Department of Forest Resources Conservation and Ecotourism - IPB University, 2022)
Kemang (Mangifera kemanga Blume.) is a local fruit and has become the identity flora of Bogor Regency based on Decree of the Regent's Number 522/185/Kpts/1996. Currently, the existence of kemang is rare, and it is worried about becoming extinct. This study aimed to identify the ethnobotany of kemang in the community of Bogor Regency and to develop a conservation strategy for kemang as the identity flora of Bogor Regency. The research was carried out from April-July 2021 in Kemang District, Sukaraja District, and Leuwiliang District. Based on criteria, the research was conducted through deeply personal interviews with the local community. The characteristic of the respondent was individual who has kemang and gardeners whose gardens contain kemang. The data obtained were analyzed descriptively. Based on interviews with 30 respondents, kemang was identified by looking at leaf color, leaf shape, stem, flower, and fruit compared to mango (Mangifera indica). Kemang mainly was found growing in gardens (74%). Kemang propagation was done by seed. The most used parts were fruit (43%) and shoots (39%). Both parts were consumed directly in a fresh form. Besides having a role as a food ingredient, kemang has potential as an antioxidant, anticancer, and anti-degenerative. The reason people still maintain kemang because the existence of kemang is getting rare, and the selling price of kemang fruit is relatively high compared to other types of mango. In addition, kemang can also prevent soil erosion. The conservation strategies of kemang are optimizing the socialization and publication of kemang benefit, developing kemang cultivation, and developing kemang as a local fruit commodity. Key words: conservation strategy, ethnobotany, kemang, local fruit, rare